2017
DOI: 10.1080/14686996.2017.1341802
|View full text |Cite
|
Sign up to set email alerts
|

The impact of Ti and temperature on the stability of Nb5Si3 phases: a first-principles study

Abstract: Nb-silicide based alloys could be used at T > 1423 K in future aero-engines. Titanium is an important additive to these new alloys where it improves oxidation, fracture toughness and reduces density. The microstructures of the new alloys consist of an Nb solid solution, and silicides and other intermetallics can be present. Three Nb5Si3 polymorphs are known, namely αNb5Si3 (tI32 Cr5B3-type, D8l), βNb5Si3 (tI32 W5Si3-type, D8m) and γNb5Si3 (hP16 Mn5Si3-type, D88). In these 5–3 silicides Nb atoms can be substitu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
53
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 40 publications
(54 citation statements)
references
References 33 publications
1
53
0
Order By: Relevance
“…The Young’s moduli of Nb, αNb 5 Si 3 , and βNb 5 Si 3 , respectively are 101.9, 291, and 269 GPa [ 40 ]. The data in Table 3 shows that the synergy of Al, Cr, and Ti had a stronger negative effect compared with the synergies between Al and Ti and between Al, Cr, Hf, and Ti.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The Young’s moduli of Nb, αNb 5 Si 3 , and βNb 5 Si 3 , respectively are 101.9, 291, and 269 GPa [ 40 ]. The data in Table 3 shows that the synergy of Al, Cr, and Ti had a stronger negative effect compared with the synergies between Al and Ti and between Al, Cr, Hf, and Ti.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, the data for the Nb 5 Si 3 in Table 3 is in agreement with the calculations that showed higher modulus for binary (unalloyed) αNb 5 Si 3 than βNb 5 Si 3 . Calculations in [ 40 ] for Nb 5 Si 3 alloyed with Ti showed that when 12.5 at.% Ti substitutes Nb in the Nb 5 Si 3 , the moduli of α(Nb 50 Ti 12.5 )Si 37.5 and β(Nb 50 Ti 12.5 )Si 37.5 were 313.8 and 238.5 GPa, respectively. The data in Table 3 for the alloy KZ7 would suggest that the substitution of Nb by Ti, and Si by Al, reduced the modulus of αNb 5 Si 3 .…”
Section: Discussionmentioning
confidence: 99%
“…The same is the case when Ge is in synergy with Al, Cr, and Hf without transition and refractory metals [34], but not the case without Hf and other transition and refractory metals [34]. The type of Nb 5 Si 3 in the microstructure is important owing to the different properties and CTE of the binary and alloyed βNb 5 Si 3 and αNb 5 Si 3 silicides [14,39].…”
Section: Introductionmentioning
confidence: 90%
“…The latter was not observed in ZF6. The Nb 5 Ge 3 has lower shear (G) and Young's (E) moduli and higher Poisson's ratio (ν) than βNb 5 Si 3 [54,59], as well as G, E, and ν values closer to the values of Ti-alloyed βNb 5 Si 3 , particularly as the Ti concentration in the silicide increases [39]. Furthermore, in the IOZ of OHS1, the concentrations of Cr and Ti were reduced significantly in the areas that were enriched in Ge and Sn below the said interface.…”
Section: Oxidation At 1200 • Cmentioning
confidence: 99%
“…The CTE (coefficient of thermal expansion) of Nb is 7.6 × 10 −6 K −1 and of Nb 3 Sn is 10.3 × 10 −6 K −1 [43]. The βNb 5 Si 3 and αNb 5 Si 3 exhibit anisotropy in CTE and the ratio of CTE values along the a and c axes of their lattices (i.e., the CTE anisotropy ratio) is different for each phase [44]. All the aforementioned values are for the unalloyed phases and are expected to change as they become alloyed [44].…”
mentioning
confidence: 99%